Improving magnetic fields in overhead transmission lines using the insulated cross-arm method - Ahsan, Matiullah; Baharom, Md Nor Ramdon; Zainal, Zainab; Sahari, Norain; Hanim, Faridah; Kamarudin, Saufi; Abd Rahman, Rashisham; Mohd Yousof, Mohd Fairouz; Jamail, Nor Akmal; Othman, Nordiana Azlin (Institute of Advanced Engineering and Science, 2024)
This research study evaluates the effectiveness of the insulated cross-arm (ICA) method in reducing magnetic field (MF) levels in transmission lines. Using Ansys Maxwell finite element method (FEM) software, the study models and analyses the MF distribution in 132 kV and 275 kV overhead transmission lines (OTLs) in Malaysia. The findings reveal that implementing the ICA method can substantially reduce MF levels, improving MF performance by 36% (at 132 kV) and 48% (at 275 kV). These findings have important implications for mitigating potential health risks associated with high MF exposure near transmission lines. Furthermore, the study highlights the potential for future enhancements in ampacity and emphasizes the importance of promoting a health-conscious environment. Field studies, assessments, and investigations into economic feasibility and practical implementation are recommended for further validation and application of the ICA method. Overall, this research study contributes to the knowledge and understanding of reducing MF exposure and improving the efficiency of power transmission systems.